The influence of audio effects and attention on the perceived duration of interaction. Issue 159 (March 2022) - Suwanaposee, Pang; Gutwin, Carl; Cockburn, Andy
Abstract : highlights: Examines the influence of audio effects on perceived duration of interactive tasks. Increasing-tempo beeps shortens perceived duration of interactive tasks. Examines the influence of interface attentional demand on perceived duration. Perceived duration is reduced with higher interface attentional demand. Shows the effect of prospective versus retrospective methodology on time perception. Abstract: Users often need to wait for computer systems to perform some task, and these delays can have adverse effects on user experience. One way to ease the problem is to use stimuli that reduce perceived wait time. We conducted a study investigating how audio effects influence users perceived wait time across three interaction contexts — passive waiting with no visual feedback, passive waiting with visual feedback (watching a progress bar), and playing a simple game. We tested three different types of audio effects: a series of beeps that changed in tempo (increasing, decreasing, or constant tempo), a series of beeps that changed in pitch (rising, falling, or constant), and variants of a polyphonic Shepard tone (an auditory illusion that seems to rise or fall in pitch continuously); a silent condition was included as a baseline. In the first stage of the experiment, participants experienced a 10.1 second wait period, indicated with a progress bar, accompanied by an audio effect. They then estimated the duration of the wait, making a retrospective assessment of the experience. In the second stage, participants experienced a series of conditions that compared two 10.1 second wait periods accompanied by different effects and selected which one (if either) felt longer, making a prospective assessment (i.e., they were aware that the two durations would be compared before experiencing them). Results from the first stage showed that perceived duration differed across different audio conditions. Results from the second stage supported prior findings that increasing-tempo beeps can shorten perceived duration and generalised the findings to interactions that include visual feedback (e.g., watching a progress bar) and those involving direct interaction (e.g., playing a simple game).